Reproducibility of rapid diagnostic tests for Trypanosoma cruzi infection in endemic areas of Colombia (2021)
Introduction: Chagas disease is a neglected tropical disease of interest to public health because of its social and economic burden. Identifying infected and sick people with Chagas disease constitutes the first step towards achieving World Health Ooganization’s goals for 2020. Objective: To evaluate the reproducibility with gold standard of a rapid diagnostic test for detection of antibodies to T. cruzi; and to propose a diagnostic algorithm for Chagas disease under the point-of-care concept in an area with limited access to health care coverage. Material and Methods: A cross-sectional study was performed to detect antibodies to T. cruzi in 151 indigenous volunteers belonging to three ethnic groups of the Sierra Nevada de Santa Marta, Colombia. Rapid tests-PDR SD BIOLINE Chagas Ab were implemented in the field versus confirmation in the laboratory using two standardized serological methods (ELISAs). Results: The results show that 19,2 % seroreactivity for T. cruzi was found among the entire population screening. The highest rate of human infection with T. cruzi was detected in the Wiwa community. No significant differences between rapid diagnostic test and the standard techniques (ELISAs) were found. Sensitivity, specificity and concordance for RDT were 100 % (Kappa: 1,0). Conclusions: The Sierra Nevada de Santa Marta continues to be a hyperendemic area for Chagas disease. The area is difficult to access and has low or no primary health care coverage, making the assessed rapid diagnostic test a useful tool for screening programs and defining treatment and control plans, which represents the first approach at establishing a point-ofcare testing strategy for endemic countries for Chagas disease.